2016
DOI: 10.3892/etm.2016.3705
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of seven breast tuberculosis cases

Abstract: Abstract. The present study aimed to evaluate the demographic data, diagnostic methods, therapeutic regimens and duration of therapy in 7 breast tuberculosis (BTB) cases. The data of BTB cases treated between January 2006 and December 2013 were retrospectively evaluated, with a total of 648 tuberculosis (TB) cases recorded during the 8-year period. Among these cases, 296 patients (50%) suffered from pulmonary TB, 278 (43%) from non-pulmonary TB and 45 (7%) from PTB plus NPTB. In total, 7 BTB were diagnosed, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…It usually occurs secondary to a centripetal lymphatic spread of M. tuberculosis from the lungs to the mammary tissue through the lymph nodes of these areas . Gumma, nodules, and draining sinus are usually unilateral, as were in our cases . Scrofuloderma and gumma were associated with skeletal system involvement .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It usually occurs secondary to a centripetal lymphatic spread of M. tuberculosis from the lungs to the mammary tissue through the lymph nodes of these areas . Gumma, nodules, and draining sinus are usually unilateral, as were in our cases . Scrofuloderma and gumma were associated with skeletal system involvement .…”
Section: Discussionsupporting
confidence: 76%
“…Gumma, nodules, and draining sinus are usually unilateral, as were in our cases . Scrofuloderma and gumma were associated with skeletal system involvement . The diagnosis in these cases took a long time, making the disease much worse, causing us to always consider the possibility of concomitant subclinical bone disease upon the diagnosis of CTB in this localization.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, hematologic spread from remote lesions or direct extension from the adjacent skin lesions might also occur [4]. Lactation, which involves increased blood flow to the mammary glands, has been reported to be a risk factor for breast tuberculosis [8]. In endemic countries, tuberculous mastitis most commonly occurs in women of reproductive age, that is, those aged 20-40 years [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Lactation, which involves increased blood flow to the mammary glands, has been reported to be a risk factor for breast tuberculosis [8]. In endemic countries, tuberculous mastitis most commonly occurs in women of reproductive age, that is, those aged 20-40 years [7,8]. However, as in this case, tuberculous mastitis can occasionally occur in elderly patients [9] and sometimes even in men [7].…”
Section: Discussionmentioning
confidence: 99%
“…Çakar and Çiledag evaluated consecutive patients treated for TB in an 8 year period from 2006 to 2013. They suggested that the incidence of mammary TB constituted 1.08% of all the patients diagnosed [2]. In India, recent reports have found the incidence of this entity to be 3-4.5% of all surgically treated breast lesions [1,3,4].…”
mentioning
confidence: 99%